IMPLEMENTATION OF THE TPACK FRAMEWORK TO MEASURE INTEGRATION OF TECHNOLOGY, PEDAGOGY AND THE CONTENT OF LECTURERS IN MATHEMATICS EDUCATION - Hepsi Nindiasari; Nena Restiana; Aan Subhan Pamungkas (FKIP Universitas Muhammadiyah Tangerang, 2021)
One of the obstacles using technology is the lack of teacher understanding of technology, therefore this study aims to determine the understanding of lecturers of mathematics education on the integration of technology in learning using the TPACK (Technological, Pedagogical, Content Knowledge) framework, a few of research that applying TPACK in universities. Furthermore, the both effect of gender and age of teaching on TPACK were analyzed on TPACK using analysis of variance (ANOVA). The results of this study are Power point applications are technologies that are widely used by mathematics education lecturers by 40.9%. PCK, PK and CK components have a strong positive effect on TPACK perceptions of mathematics education lecturers. The average value of TPACK components is TK 3.95; CK 4.01; PK 4.08; 4.02 PCK; TCK 4.04; TPK 4.02; TPACK 3.96. For an in-depth analysis of gender and age of teaching factors on the TPACK component. This study found that gender and duration of teaching was no significant influence between the understanding of mathematics education lecturers and the seven components of TPACK.